Conjugative DNA Transfer From E. coli to Transformation-Resistant Lactobacilli - Samperio, Sara; Guzmán-Herrador, Dolores L.; May-Cuz, Rigoberto; Martín, Maria Cruz; Álvarez, Miguel A.; Llosa, Matxalen (Frontiers in Microbiology, 2021)
Lactic acid bacteria (LAB) belonging to the genus classically known as Lactobacillus, recently split into 25 different genera, include many relevant species for the food industry. The well-known properties of lactobacilli as probiotics make them an attractive model also for vaccines and therapeutic proteins delivery in humans. However, scarce tools are available to accomplish genetic modification of these organisms, and most are only suitable for laboratory strains. Here, we test bacterial conjugation as a new tool to introduce genetic modifications into many biotechnologically relevant laboratory and wild type lactobacilli. Using mobilizable shuttle plasmids from a donor Escherichia coli carrying either RP4 or R388 conjugative systems, we were able to get transconjugants to all tested Lactocaseibacillus casei strains, including many natural isolates, and to several other genera, including Lentilactobacillus parabuchneri, for which no transformation protocol has been reported. Transconjugants were confirmed by the presence of the oriT and 16S rRNA gene sequencing. Serendipitously, we also found transconjugants into researcher-contaminant Staphylococcus epidermidis. Conjugative DNA transfer from E. coli to S. aureus was previously described, but at very low frequencies. We have purified this recipient strain and used it in standard conjugation assays, confirming that both R388 and RP4 conjugative systems mediate mobilization of plasmids into S. epidermidis. This protocol could be assayed to introduce DNA into other Gram-positive microorganisms which are resistant to transformation.